“The Mirror Crack’d”: Representation of Characters in Terry Pratchett’s Witches Abroad - Mussa, Jumana (Humaniora. Czasopismo Internetowe, 2019)
The current article presents a discussion of two characters in Terry Pratchett’s Witches Abroad (1990), Esmeralda and Lily Weatherwax. These two sisters are almost mirror images of each other, yet each takes a different path in life. Through their similarities and differences, one is able to examine the idea of uncanny repetition, as it was discussed by Jacques Derrida and Gilles Deleuze. Through the characters’ choices and interaction with each other, one may also be able to explore their identities, as imperfect mirror reflections that contradict and inform each other.